A new Creagrutus from the upper rio Xingu basin, Brazil (Teleostei: Characiformes: Characidae) - Flausino Jr, Nelson [UNESP]; Lima, Flavio C. T. (Acad Natural Sciences Phila, 2017)
A new species of Creagrutus is described from the upper rio Xingu basin, Mato Grosso state, BraziL The new specks can be distinguished from its congeners by a combination of characters that includes dorsal tin mostly black, a dark oblique blotch on middle and upper-inferior caudal-fin rays, and presence of only two rows of premaxillary teeth. Creagrutus mucipu, formerly known only from the upper rio Tocantins basin in Brazil, is recorded herein as occurring syntopically with the new species in the upper rio Xingu basin.